HUBUNGAN PENGETAHUAN DAN PERAN SERTA PETUGAS KESEHATAN DENGAN KEPATUHAN IBU HAMIL TRIMESTER I TERHADAP CAPAIAN KUNJUNGAN PERTAMA (K1) - Aisyah, Siti; Arita, Ipak; Noprianti, Noprianti (JURNAL KESEHATAN TERAPAN, 2021)
Background: First visit (K1) is the contact of pregnant women for the first time with health workers for health checks and health services in the first trimester, where the pregnancy is 1 to 12 weeks, including identity / bio, pregnancy history, obstetric history, medical history, history. Socioe conomic, and pregnancy. Objective: to see the relationship between knowledge and participation of health workers with pregnant women in the first trimester of the first visit (K1). Methods: This type of research used a cross sectional study design with sampling using simple random sampling obtained 56 respondents. Results: it was found that there was a significant relationship between knowledge (PV value = 0.016> α = 0.05), income (PV value = 0.012> α = 0.05), the role of health workers (PV value = 0.003> α = 0.05) First visit (K1) achievements. Suggestion: increase information to pregnant women who discuss the importance of checking their pregnancies in the first trimester by providing information that is conveyed in the form of counseling to mothers, namely through direct communication media or with assistance. Keywords: Compliance of 1st Trimester Pregnant Women